2014
DOI: 10.1364/oe.22.012461
|View full text |Cite
|
Sign up to set email alerts
|

Sub-50-fs pulse generation from thulium-doped ZBLAN fiber laser oscillator

Abstract: An ultrafast, passively mode-locked fiber laser oscillator has been realized using thulium-doped ZBLAN fibers. Very low dispersion of ZBLAN glass fibers enabled generation of pulses with broad spectra extending from 1730 nm to 2050 nm. Pulses are obtained with the average power of 13 mW at the repetition rate of 67.5 MHz when the pump power is 140 mW. The output pulses are compressed with a pair of SF10 prisms and their durations are measured with SHG FROG, from which we obtained the pulse duration as short as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 26 publications
(29 reference statements)
0
15
1
Order By: Relevance
“…Sub-500 fs pulses were realized in the first soliton Tm fiber laser back in 1995 [2]. Pulse durations as short as ∼50 fs have been achieved in dispersion-managed cavities, with pulse energy <1 nJ [3,4]. A cavity containing a grating and telescope combination for the normal-dispersion segment generated 5.4-nJ and 216-fs pulses [5].…”
mentioning
confidence: 99%
“…Sub-500 fs pulses were realized in the first soliton Tm fiber laser back in 1995 [2]. Pulse durations as short as ∼50 fs have been achieved in dispersion-managed cavities, with pulse energy <1 nJ [3,4]. A cavity containing a grating and telescope combination for the normal-dispersion segment generated 5.4-nJ and 216-fs pulses [5].…”
mentioning
confidence: 99%
“…However, the property of low dispersion has been overlooked in the previous research on ZBLAN fibers. Recently, the authors demonstrated a thuliumdoped fiber laser oscillator based on ZBLAN fibers pumped by a Ti:sapphire laser, and pulses as short as 45 fs are generated [27].…”
Section: Introductionmentioning
confidence: 99%
“…Two types of oscillators are demonstrated using two different types of fibers. One is made with a single-mode ZBLAN fiber, which is a system similar to that presented in [27] but the Ti:sapphire laser used as the pump is replaced with laser diodes. The other is a completely new system built with doubleclad ZBLAN fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of commercially available mid-IR resonant gain media, there have been only a few reports of fs-lasers developed beyond a wavelength of 2.5 μm [3,4]. Although 2 μm fiber lasers have been developed in the fs regime [5], to go further into the mid-IR requires frequency conversion. Different frequency generation (DFG) is an option [6], but typically has low efficiency Synchronously pumped optical parametric oscillators (OPOs) are recognized as useful laser sources for the production of tunable output pulses over a broad wavelength range including the mid-IR [7][8][9].…”
Section: Introductionmentioning
confidence: 99%